Studi Etnobotani Tumbuhan Obat-Obatan Tradisional Suku Melayu di Desa Mungguk Kecamatan Sekadau Hilir Kabupaten Sekadau - Selpi, Selpi; Turnip, Masnur; -, Rafdinal (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2024)
Medicinal plants are plants that contain active substances that can be utilized as disease healers as well as medicinal properties. The utilization of medicinal plants has been widely practiced by the Malay community in Mungguk Village. The purpose of this study was to determine the number of species with medicinal properties, plant parts, processing methods and the use value of medicinal plants. This research was conducted from March to April 2023 located in Mungguk Village, Sekadau Regency, West Kalimantan. This research used semi-structured interview techniques with sample collection using the snowball sampling method. The results of the research on potential medicinal plants in Mungguk Village found 35 species in 20 families. The frequency of citation of families with the largest utilization value was 70% in the Zingiberaceae family, while the lowest was 10% in the Amaryllidaceae family, Lauraceae family, Malvaceae family, and Pedaliaceae family. The highest species use value (SUV) was 0.5 and the lowest was 0.1.